Exploring the adverse impact of social media use among secondary school students in Malaysia - Ismail, Halim; Mamat, Arifin; Ibrahim, Hasniza; Mokhtar, Nazatul Akmar; Zailan, Noor Aiman (Technoarete Group, 2025)
In today’s hyper-connected society, social media has become both an essential and potentially disruptive element in the lives of Malaysian secondary school students. This study examines the adverse effects of social media engagement on adolescents, with a particular focus on character decline. Data were collected through four semi-structured individual interviews and one group interview involving eight secondary school students in Kuala Lumpur, Malaysia. The analysis revealed three central themes: (1) time management, (2) self-discipline, and (3) mindset. Within time management, two subthemes emerged: (i) wasted time and (ii) interference with completing schoolwork, revision, or household duties. Uncontrolled use of social media was also shown to weaken self-discipline, with two subthemes identified: (i) addiction and (ii) neglecting meaningful routines, resulting in unproductivity. Regarding mindset, unrestricted access to online platforms was found to hinder adolescents’ cognitive and psychological growth. Subthemes included (i) misleading content, (ii) spreading harmful rumours, and (iii) exposure to inappropriate material. These findings highlight the urgency of joint action among policymakers, educators, parents, and community organisations to address character erosion and foster disciplined, balanced, and emotionally resilient youth.